2015
DOI: 10.1037/adb0000090
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patient retention in methadone maintenance treatment.

Abstract: This study sought to determine whether select pretreatment demographic and in-treatment clinical variables predict premature treatment discharge at 6 and 12 months among patients receiving methadone maintenance treatment (MMT). Data were abstracted from electronic medical records for 1,644 patients with an average age of 34.7 years (SD = 11.06) admitted to 26 MMT programs located throughout the United States from 2009 to 2011. Patients were studied through retrospective chart review for 12 months or until trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 66 publications
8
46
1
Order By: Relevance
“…In keeping with previous evidence,12,58,59 our study showed that cocaine use is also associated with continued opioid use while on MMT. Conversely, decreased cocaine use has been associated with cessation of illicit opioid use 60.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with previous evidence,12,58,59 our study showed that cocaine use is also associated with continued opioid use while on MMT. Conversely, decreased cocaine use has been associated with cessation of illicit opioid use 60.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that responding to OAT dosing, which is clinically indicated for increased craving or polysubstance use, was inflexible and oftentimes misguided by prescribers further supports guideline-based OAT prescribing. There is now considerable evidence that documents higher retention when patients are prescribed methadone rather than buprenorphine and higher methadone doses that exceed 80mg to 100mg per day (Bao et al, 2009; Booth, Corsi, & Mikulich-Gilbertson, 2004; Farre, Mas, Torrens, Moreno, & Cami, 2002; Hser et al, 2014; Maxwell & Shinderman, 1999; Peles et al, 2006; Proctor et al, 2015; Simoens, Matheson, Bond, Inkster, & Ludbrook, 2005; Strain, Bigelow, Liebson, & Stitzer, 1999; Wickersham, Zahari, Azar, Kamarulzaman, & Altice, 2013). Instead, Ukrainian clients report that either inadequate or compete lack of response by Ukrainian OAT prescribers interfered (consciously or unconsciously) with the success of a client's treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics such as younger age, male gender, and unemployment have been found to negatively impact OAT retention (Che et al, 2010; Jiang et al, 2014; Proctor et al, 2015; Strike et al, 2005) while unmarried patients or those without a supportive network were more likely to experience a poor outcome with respect to OAT retention (Che et al, 2010; Yang, 2013). Clinical factors, including addiction severity and medication dosing and type of medication received (methadone vs buprenorphine/naloxone) were found to be predictors of OAT retention (Bao et al, 2009; Che et al, 2010; Peles, Schreiber, & Adelson, 2006; Proctor et al, 2015). Structural issues such as distance to and accessibility of clinic site have also been shown to predict discontinuation of OAT (Che et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Older age may be a predictor of treatment retention because older patients have had more treatment episodes, which cumulatively increase the likelihood of treatment retention 51 . Younger patients, who have not experienced as many substance-related negative consequences relative to older patients 32 , are more likely to drop out early from methadone maintenance and opiate agonist treatment 13,15,16,27,49,52 . Racial/ethnic minorities are more likely to drop out of treatment early 29,52 , suggesting the need for further research to improve treatment retention.…”
Section: Discussionmentioning
confidence: 99%
“…Non-white racial/ethnic group membership predicts early drop out 1,15 . Gender has not consistently predicted entry or retention 1,2931 , although there is some evidence to suggest that men are more likely to be retained 28,32 . While some studies have found treatment readiness for cessation of drug use to be an important influence on retention 11 in different treatment modalities (e.g., long term residential, outpatient, methadone) 20,25,33,34 , others have not found this relationship 35,36 , particularly among samples of African-American patients 35,37 .…”
Section: Introductionmentioning
confidence: 97%